Analysis of serum levels L-arginine and 25-hydroxyvitamin D as a predictor of survival of severe preeclampsia mothers - Dwi Wahyuningsih; Andi Nilawati Usman; Prihantono (Elsevier, 2021)
Objective: This study aimed to analyze serum levels of L-arginine and 25-hydroxyvitamin D as predictors of survival in severely preeclamptic women. Methods: This study is a retrospective descriptive study using medical record data from June to August 2019 and has received a recommendation for ethical approval with the protocol number UH20070290. The study was conducted in 4 hospitals in Makassar: Dr. General Hospital. Wahidin Sudirohusodo, Hasanuddin University Teaching Hospital, Siti Fatimah Regional Mother and Child Health Hospital, and Sitti Khadijah 1 Mother and Child Hospital. The samples of this study were mothers who gave birth with a diagnosis of normal pregnant women, severe preeclampsia, and severe preeclampsia with complications. Results: Serum l-arginine level did not affect the survival of severe preeclamptic mothers. It was shown at p-value 0.799 > 0.05. Meanwhile, serum levels of 25-hydroxyvitamin D affect the predictors of maternal preeclampsia where the p-value is 0.024 < 0.05. In comparing serum levels of L-arginine and 25-hydroxyvitamin D, there was no significant difference in groups of normal pregnant women, severe preeclampsia, and severe preeclampsia with complications. Conclusion: Serum level of 25-hydroxyvitamin affects the survival of severe preeclamptic mothers.